2009
DOI: 10.1002/ijc.24232
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral contraceptives, intrauterine devices and tubal sterilization and cancer risk in a large prospective study, from 1996 to 2006

Abstract: The association of contraceptive methods, including oral contraceptives (OC), intrauterine devices (IUD) and tubal sterilization (TS), with overall and site-specific cancer were prospectively investigated in a cohort of 66,661 Chinese women in Shanghai, 76.7% of whom used contraception. During a median follow-up time of 7.5 years, 2,250 women were diagnosed with cancer. Everuse of any contraceptive method was not associated with overall cancer risk [adjusted hazard ratio (HR adj ) 5 1.02, 95% CI, 0.92-1.12]. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 79 publications
3
68
4
1
Order By: Relevance
“…Reports of the relationship between tubal ligation and breast cancer risk have been varied, including suggestions of either a reduced Calle et al, 2001) or increased risk (Irwin et al, 1988), although the majority of studies reported no significant association Eliassen et al, 2006;Iversen et al, 2007;Dorjgochoo et al, 2009;Press et al, 2011;Gaudet et al, 2013;Nichols et al, 2013), consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Reports of the relationship between tubal ligation and breast cancer risk have been varied, including suggestions of either a reduced Calle et al, 2001) or increased risk (Irwin et al, 1988), although the majority of studies reported no significant association Eliassen et al, 2006;Iversen et al, 2007;Dorjgochoo et al, 2009;Press et al, 2011;Gaudet et al, 2013;Nichols et al, 2013), consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…The strongest association was with a history of cervical intraepithelial neoplasia grade 3 (RR ¼ 4.03, 95% CI: 2.59-6.28), reflecting the importance of high-risk strains of human papilloma virus as causative agents of both cervical (Walboomers et al, 1999) example, as tubal ligation is usually performed for permanent contraception, it is likely to be more common among women who are sexually active, and who thus may be more likely to be exposed to sexually-transmitted infections, such as human papilloma virus, and the consequent increased risk of anal cancer. There have been reports on possible relationships between tubal ligation and other cancers, including possible reductions in risk of colorectal (Cape and Kreiger, 1999;Rosenblatt et al, 2004) and stomach cancer (Dorjgochoo et al, 2009), and increased risks of thyroid cancer (Braganza et al, 2014) and lymphatic and haematopoietic malignancies (Kjaer et al, 2004). We did not replicate any of these findings.…”
Section: Discussioncontrasting
confidence: 56%
“…Female sex (19), use of contraceptive pills (46), and oral hormonal replacement therapy (25) are associated with high risk of gallbladder cancer, indicating a strong role for estrogens in the carcinogenesis process of this organ. Only female LXRβ −/− animals demonstrate preneoplastic lesions and the elimination of estrogens with ovariectomy prevents the formation of these lesions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies (4 good, 6 fair, 1 poor quality) evaluated the association between oral contraceptive use and colorectal cancer incidence (63,65,66,68,(88)(89)(90)(91)(92)(93)(94)(95). Of these, 3 were case-control studies, 7 were cohort studies, and 1 was a pooled analysis.…”
Section: Colorectal Cancer Incidencementioning
confidence: 99%